2007
DOI: 10.1099/jmm.0.47094-0
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo dynamics of Streptococcus spp., Actinomyces naeslundii, Fusobacterium nucleatum and Veillonella spp. in dental plaque biofilm as analysed by five-colour multiplex fluorescence in situ hybridization

Abstract: The in vivo dynamics of Streptococcus spp., Actinomyces naeslundii, Fusobacterium nucleatum and Veillonella spp. in dental plaque biofilm as analysed by five-colour multiplex fluorescence in situ hybridizationAli Al-Ahmad, 1 The formation and composition of dental plaque biofilm in vivo are important factors which influence the development of gingivitis, caries and periodontitis. Studying dental plaque biofilm in in vitro models can cause an oversimplification of the real conditions in the oral cavity. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 42 publications
3
120
0
2
Order By: Relevance
“…Also, owing to the microenvironments that facilitate cell-cell communication, another physical parameter, biofilm thickness, might be a good predictor of in vivo behavior. Dental biofilm thicknesses have been shown to grow to approximately 50 μm after 1 week (Al-Ahmad et al 2007), while mature biofilms recovered from urinary catheters can range between 3 and 490 μm, depending on the formative species (Ganderton et al 1992). A mouse model of thermal injury showed mature, 11-μm-thick P. aeruginosa biofilms at 46 h (Schaber et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Also, owing to the microenvironments that facilitate cell-cell communication, another physical parameter, biofilm thickness, might be a good predictor of in vivo behavior. Dental biofilm thicknesses have been shown to grow to approximately 50 μm after 1 week (Al-Ahmad et al 2007), while mature biofilms recovered from urinary catheters can range between 3 and 490 μm, depending on the formative species (Ganderton et al 1992). A mouse model of thermal injury showed mature, 11-μm-thick P. aeruginosa biofilms at 46 h (Schaber et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Image analysis was performed as described elsewhere (27). The program LSM Image Browser (Zeiss, Oberkochen, Germany) was utilized to yield the maximal projection of each image stack and, hence, to quantify the covering grades of the scanned biofilm points.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 However, these studies were primarily qualitative, relying on microscopic observations of biofilm formation, and the data are insufficient to acquire a detailed understanding of the mechanism of dental biofilm formation. Further, previous studies found that dental biofilm formation increases bacterial diversity and alters the predominant bacterial species present over time, which changes the environment in which oral disease develops.…”
Section: Introductionmentioning
confidence: 99%